Penerapan Problem Solving Model SSCS Terhadap Creative Thinking skill Peserta Didik Materi Kesetimbangan dan Elastisitas Kelas XI SMAN 12 Padang - Adli Dzil Ikhram; Djusmaini Djamas; Ramli Ramli (Universitas Negeri Padang, 2018)
The low creative thinking skill Students SMAN 12 Padang one of the causes is the students tend to passively in the learning because of learning centered on educators. Therefore, research is done in order to give one solution by applying Problem Solving Approach Model SSCS. Learning with Problem Solving approach SSCS model enables learners to be actively involved and engage in creative thinking processes. Implementation of problem solving in learning process will stimulate and develop creative thinking skill. This research has a goal for investigate the influence of solution to problem Approach Model SSCS Against Creative Thinking Skill of Students on Matter of Equilibrium and Elasticity of Class XI SMAN 12 Padang. To achieve research objectives,We have done using quasi-experiments. The object of this research is the learner of classification XI MIA in SMAN 12 Padang register in the academic year 2017/2018. Sampling in this research based on Purposive Sampling technique. The result obtained in the form of data creative thinking skills that are seen in the results of knowledge competence. The research instrument is a final test sheet in the form of essay knowledge competence. Technique of data analysis through equality test of two mean with t test statistic on knowledge competence. After obtaining the data, the researcher sees a difference from the average creative thinking skill between the two sample classes. The experiment class has an average of 72.09. The average is higher than the control class. The control class has an average of 68.72. The result of tcount test 2,3807 with ttable 2.0003 shows thitung is outside the acceptance area of Ho, meaning that Hi is accepted, there is a significant influence of Problem Solving Model SSCS Against Creative Thinking Skill of Student on Matter of Equilibrium and Elasticity of Class XI SMAN 12 Padang at a significant level of 0.05.